A fully autonomous integrated interface circuit for piezoelectric harvesters - Hehn, Thorsten (2013)
This paper presents a fully autonomous, adaptive pulsed synchronous charge extractor (PSCE) circuit optimized for piezoelectric harvesters (PEHs) which have a wide output voltage range 1.3-20 V. The PSCE chip fabricated in a 0.35 μm CMOS process is supplied exclusively by the buffer capacitor where the harvested energy is stored in. Due to the low power consumption, the chip can handle a minimum PEH output power of 5.7 μW. The system performs a startup from an uncharged buffer capacitor and operates in the adaptive mode at storage buffer voltages from 1.4 V to 5 V. By reducing the series resistance losses, the implementation of an improved switching technique increases the extracted power by up to 20% compared to the formerly presented Synchronous Electric Charge Extraction (SECE) technique and enables the chip efficiency to reach values of up to 85%. Compared to a low-voltage-drop passive full-wave rectifier, the PSCE chip increases the extracted power to 123% when the PEH is driven at resonance and to 206% at off-resonance.